Baduanjin exercise for low back pain: A systematic review and meta-analysis. (April 2019) - Li, Huanan; Ge, Di; Liu, Siwen; Zhang, Wei; Wang, Jingui; Si, Jinhua; Zhai, Jingbo
Highlights: Baduanjin is very popular and widely practiced for the management of LBP. This study systematically evaluated the efficacy and safety of Baduanjin for LBP. No large effects on pain or back-specific function were identified. It suggests that Baduanjin is effective for LBP. However, more large-scale, well-designed RCTs are warranted. Abstract: Introduction: Low back pain (LBP) is one of the most common public health concerns worldwide. Baduanjin is very popular and widely practiced for the management of LBP. This study aims to systematically investigate the efficacy and safety of Baduanjin exercise for patients with LBP. Methods: The PubMed, EMBASE, CENTRAL, Web of Science Core Collection, CBM, CNKI, WANFANG and VIP databases were searched from inception to August 2018 to identify potentially eligible studies. Risk of bias was assessed with the Cochrane collaboration's tool. All statistical analyses were conducted with the RevMan 5.3 software. Results: Nine studies involving 519 patients were included in this systematic review. Our meta-analysis showed that Baduanjin was associated with a small improvement in pain relief compared with general exercise (MD= -0.50, 95% CI: -0.86 to -0.15, P = 0.005). One trial indicated that Baduanjin was superior to routine drug (ibuprofen) in alleviating pain, and the effect was moderate (MD= -1.04, 95% CI: -1.52 to -0.56, P < 0.0001). A descriptive analysis showed that Baduanjin plus other active treatments (such as massage, suspension, or routine drug plus general exercise) had small to moderate effects on low back pain relief compared with active treatments alone. One trial reported that Baduanjin decreased the Oswestry Disability Index (ODI) score compared with routine drug (MD= -4.92, 95% CI= -7.81 to -2.03, P = 0.0009). Another trial found the combination of Baduanjin and electrotherapy offered better improvement than electrotherapy on back-specific function (MD= -6.03, 95% CI= -8.45 to -3.61, P < 0.00001). Three trials suggested that Baduanjin alone or in combination with other treatments achieved greater effects on the Japanese Orthopaedic Association (JOA) score improvement than other treatments. No adverse event was identified in the only study reporting on safety data. Conclusions: The present study indicated that Baduanjin is effective for LBP. However, evidence supporting the finding is limited due to the small sample size, potential methodological flaws and significant heterogeneity. More large-scale, well-designed RCTs are warranted.